1994
DOI: 10.1111/j.1540-8191.1994.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Surgical Techniques for Aneurysms of the Descending Thoracic Aorta: Twenty-Nine Years Experience with 659 Patients

Abstract: Between 1953 and 1993, 659 patients underwent descending thoracic aneurysm resection. The most common etiology was atherosclerosis. Pain was the main presenting symptom. Perioperative mortality fell from 24.2% between 1953 and 1964 to 14.3% between 1970 and 1993. Paraplegia occurred in 4.1% (27/659) patients overall and was little affected by time of operation or use of atriofemoral bypass. Paraparesis occurred in 5.9% (39/659) patients and was reduced by use of atriofemoral bypass. The low rate of paraparesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 23 publications
0
32
1
Order By: Relevance
“…In contrast to the spinal ischemic event rate with open repair reported in other multicenter TEVAR studies, 12 the rate of spinal ischemic events in the open group from this study appeared to be largely comparable with those reported in several large single-center experiences (1.5%-6.3%), 2,6,[13][14][15] even though 28 institutions contributed at least one open patient. Nonstatistically significant differences between open and TEVAR in spinal ischemic events have been reported previously.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast to the spinal ischemic event rate with open repair reported in other multicenter TEVAR studies, 12 the rate of spinal ischemic events in the open group from this study appeared to be largely comparable with those reported in several large single-center experiences (1.5%-6.3%), 2,6,[13][14][15] even though 28 institutions contributed at least one open patient. Nonstatistically significant differences between open and TEVAR in spinal ischemic events have been reported previously.…”
Section: Discussioncontrasting
confidence: 54%
“…The incidence of PGI ranges between 0.5-5%3) and secondary AEF after TEVAR ranges from 0.5% to 1.7% 4). Prompt diagnosis of these complications is critical due to the high mortality rate, ranging from 20% to 40% 5).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been showed that aortic cross-clamping time is a main predictor of postoperative spinal cord dysfunction (4, 5), a cross-clamp time over 30 min being associated with a signi cantly increased risk of paraplegia (5,65,66). Indeed, without distal aortic perfusion and any other neuroprotective methods such as hypothermia and cerebrospinal uid monitoring and drainage the risk of spinal cord ischemic injury is greatly increased (67).…”
Section: Clamp-and-sew Techniquementioning
confidence: 96%